A novel biodegradable arsenic adsorbent by immobilization of iron oxyhydroxide (FeOOH) on the root powder of long-root Eichhornia crassipes. (February 2018) - Lin, Sen; Yang, Hongjun; Na, Zhiye; Lin, Kuangfei
Abstract: In this study, FeOOH was immobilized on the biodegradable root powder, abbreviated as RP, of long-root Eichhornia crassipes, a kind of waste biomass, to improve the adsorption performances for aqueous arsenic contaminants. The adsorption kinetics and thermodynamics experiments showed that the adsorption rates and capacities of the root powder for arsenate (As(V)) and arsenite (As(III)) were both enhanced markedly after modification with FeOOH. The adsorption of As(V) and As(III) by the modified root powder, abbreviated as MRP, could arrive at equilibrium in 50 min and the saturated adsorption capacities reached up to 8.67–9.43 mg/g for As(V) and 5.21–5.65 mg/g for As(V) at temperature of 10–50 °C, respectively. Besides, the effect of pH and ionic strength on adsorption was investigated and the results showed that the optimum pH for the arsenic adsorption using the MRP was 9.0 and the As(V) adsorption was more sensitive to ionic strength. Furthermore, the complexation of hydratable hydroxyls on FeOOH with arsenic contaminants was concluded as the adsorption force according FTIR and XPS analyses. The MRP used could be regenerated via 0.4 mol/L NaOH solution and no apparent adsorption capacity losses appeared after 6 cyclic utilizations. Highlights: MRP showed great adsorption performance for As(V) and As(III). FeOOH formed on RP had better dispersion, stability and arsenic adsorption. The application of long-root Eichhornia crassipes was developed further.